1973
DOI: 10.1126/science.180.4084.410
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Producing Neuroepithelial Bodies in Rabbit Respiratory Mucosa

Abstract: The intrapulmonary lining epithelium of rabbits contains newly identified corpuscles composed of argyrophil, argentaffin, yellow fluorescent, ultrastructurally granulated and innervated epithelial cellular organs. These are proved, by electron microscopic cytochemistry and microspectrography, to be a source for intrapulmonary production of serotonin. Probably they are intrapulmonary neuroreceptor organs modulated by the central nervous system which exhibit local secretory activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…A 5-hydroxytryptaminergic neural innervation allowing EFS-evoked release of 5-HT also appears unlikely, as selective 5-HT receptor antagonists alone had no effect on EFS-induced excitatory NANC bronchoconstriction with the stimulation parameters we have tested. However this does not rule out the in vivo presence of endogenous 5-HT either from neuroepithelial cells, as in the rabbit (Lauweryns et al, 1973) or released from platelets activated during tissue damage. This released 5-HT may then serve to offset neurogenic inflammation resulting from sensory nerve activation.…”
Section: Discussionmentioning
confidence: 99%
“…A 5-hydroxytryptaminergic neural innervation allowing EFS-evoked release of 5-HT also appears unlikely, as selective 5-HT receptor antagonists alone had no effect on EFS-induced excitatory NANC bronchoconstriction with the stimulation parameters we have tested. However this does not rule out the in vivo presence of endogenous 5-HT either from neuroepithelial cells, as in the rabbit (Lauweryns et al, 1973) or released from platelets activated during tissue damage. This released 5-HT may then serve to offset neurogenic inflammation resulting from sensory nerve activation.…”
Section: Discussionmentioning
confidence: 99%
“…Eaton and Fedde (57) identified two distinct populations of amine-containing cells in the mouse lung without preincubation with amine precursors; one population emitted a yellow fluorescence and the other a yellow-green fluorescence, which was possibly due to dopamine or norepinephrine. However, yellow fluorescence is the most often reported emission in lung neuroendocrine cells (18,29). Hage (4) reported that some cells of the bronchial mucosa of human fetuses exhibited a green fluorescence.…”
Section: Cytochemistrymentioning
confidence: 99%
“…There are lung epithelial cells in some species that contain enough endogenous biogenic amine to permit detection without prior administration of the amine precursor. NEBs of fetal or neonatal rabbits, for instance, reveal yellow fluorescent cells indicative of serotonin (29) (Fig. 13).…”
Section: Cytochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…So far, these neuroendocrine epithelial (NEE) cells have been characterized primarily by morphological aspects and by their content of various peptides and amines (e.g Lauweryns et al, 1972;Cutz et al, 1975;1981;Track & Cutz, 1982;Polak & Bloom, 1982;Scheuermann, 1987;Adriaensen & Scheuermann, 1993). 5-Hydroxytryptamine (5-HT) is an important amine in the NEE cells (Dey et al, 1981;Lauweryns et al, 1973; where it appears to be stored in dense core vesicles (i.e. secretory granules of the NEE cells) (Owman et al, 1973;Cutz et al, 1975;Scheuermann, 1987;Adriaensen & Scheuermann, 1993).…”
Section: Introductionmentioning
confidence: 99%